Salivary Cortisol and Total Antioxidant Capacity (TAC) as Biomarkers of Stress in Dental Medicine Students—A Pilot Study - Otilia Bolos; Vanessa Bolchis; Ramona Dumitrescu; Vlad Tiberiu Alexa; Berivan Laura Rebeca Buzatu; Anca Marcu; Catalin Marian; Paula Diana Ciordas; Daniela Jumanca; Atena Galuscan; Octavia Balean (Medicina)
Background and Objectives: Stress is a significant issue among dental students, with both psychological and physiological impacts affecting their academic performance. This cross-sectional study aimed to explore the relationship between academic stress and salivary biochemical markers, specifically cortisol and total antioxidant capacity (TAC), in third- and fifth-year dental students during the 2022/2023 academic year. Materials and Methods: This study included 44 participants from the Faculty of Dental Medicine at Victor Babes University, Romania. Saliva samples were collected during a low-stress period and prior to exams (high-stress period). Results: Cortisol and TAC levels were measured using ELISA and TAC assays, respectively, decreasing from an average of 3.69 (SD ± 1.49) before stress to 2.86 (SD ± 2.28) during high-stress periods (p < 0.05), while salivary cortisol levels showed a non-significant change from 23.69 (SD ± 35.6) ng/mL to 20.44 (SD ± 23.07) ng/mL; additionally, female participants exhibited a mean STAI score of 91.65 (SD ± 5.13) compared to 91.09 (SD ± 9.41) for males, indicating greater stress responses among females. Conclusions: The State-Trait Anxiety Inventory (STAI) scores confirmed elevated anxiety levels during exams. The findings suggest that academic stress negatively impacts TAC while triggering a moderate increase in salivary cortisol, underlining the need for stress management interventions in dental education.